Continuity and volume of bone cement and anti osteoporosis treatment were guarantee of good clinical outcomes for percutaneous vertebroplasty: a multicenter study - Zhen Cheng; Guangzong Ren; Ziyi Li; Xianda Gao; Di Zhang; Guiyue Chen (BMC Musculoskeletal Disorders)
Abstract Background As the most prevalent fragility fracture caused by osteoporosis, increasing attention was paid to vertebral compression fractures (VCF) day by day. Percutaneous vertebroplasty (PVP) had unique advantages in treatment of VCF and was used widely. However, there were still part patients suffering from residual or unrelieved pain after the surgery. The purpose of our study was to identified the associated factors for good clinical outcomes and provide evidence for surgical strategy. Material and methods 186 patients who underwent PVP from January 2021 to January 2023 were reviewed retrospectively in the study. The patients were divided into two groups according to clinical outcomes. Preoperative general data and surgical data were collected for statistical analysis. Multivariate logistic regression analysis and the receiver operating characteristic curve were used to identify the associated factors with good clinical outcomes. Results There were statistically significant differences between two groups in volume of bone cement (p = 0.012), standardized treatment for osteoporosis (p = 0.004) and bone cement continuity (p = 0.006). The associated factors with good clinical outcomes after PVP were continuous bone cement (OR = 2.237, 95% CI = 1.191–4.201, p = 0.012), standardized treatment for osteoporosis (OR = 2.105, 95% CI = 1.089–4.068, p = 0.027) and volume of bone cement > 5.5 ml (OR = 1.271, 95% CI = 1.023–1.579, p = 0.030). Conclusion PVP effectively released the back pain of patients and was worthy of promotion. However, postoperative residual pain was an important factor that reduced the clinical outcomes. Continuous bone cement and standardized treatment for osteoporosis were guarantee of good clinical outcomes for PVP and injected bone cement > 5.5 ml might be a guarantee.